2020
DOI: 10.7759/cureus.11876
|View full text |Cite
|
Sign up to set email alerts
|

The “Kickstand Rod” Technique for Coronal Imbalance in Patients With Spinal Deformity: A Case Report With Review of Literature

Abstract: Coronal imbalance is a type of spinal deformity with deviation from midline in the coronal plane. It is challenging to correct even in the hands of experienced spine surgeons. Many conventional techniques lead to unsuccessful results or complications. However, the incorporation of "kickstand rod" (KR) instrumentation is now understood to provide a more supported coronal correction and improve spinal deformities. Sometimes it can be used to provide additional spinal support in instances where spinal fusion has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In biomechanical studies, accessory rods help maintain correction and limit the range of motion across the instrumented spinal segment [ 29 , 30 ]. The kickstand rod provides a theoretical additional advantage of correction of the scoliotic curve in patients with ASD, along with the less invasiveness of the procedure and additional biomechanical support in long posterior constructs [ 31 ] ( Fig. 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In biomechanical studies, accessory rods help maintain correction and limit the range of motion across the instrumented spinal segment [ 29 , 30 ]. The kickstand rod provides a theoretical additional advantage of correction of the scoliotic curve in patients with ASD, along with the less invasiveness of the procedure and additional biomechanical support in long posterior constructs [ 31 ] ( Fig. 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The KR technique used in this study was first described in a case report by Makhni et al in 2018 [22]. Other studies have also demonstrated its usefulness [25,[37][38][39]. However, the measures used in this study, such as RR and SD, have not been described in previous studies.…”
Section: Measures For CImentioning
confidence: 98%
“…Vector forces are then applied to the opposite side of the coronal deviation, which depresses the ipsilateral pelvis and improves coronal correction. 12,13 Although multiple studies have demonstrated the efficacy of the KSR technique in restoring coronal alignment, 3,4,[14][15][16][17] an in-depth, step-by-step description of how to implement the technique is lacking. In addition, reports with intraoperative images and videos are sparse.…”
mentioning
confidence: 99%